KONSEP AL-MUWALAH DAN ANALISIS CORAK TAFSIR AL-MUNIR - Ismatullah, Ahmad; Usman, Zulkifli Abdurrahman; Fisa, Triansyah (Prodi Ilmu Al-Qur'an dan Tafsir, 2021)
This article discusses the concept of al-muwalah and the style of interpretation of al-Munir by Wahbah az-Zuhayli. The method used is a qualitative descriptive approach with an interdisciplinary interpretation study approach. The primary source for the discussion of this article is al-Munir's interpretation which was obtained from the library. The finding of this article is that az-Zuhayli's interpretation of the concept of al-muwalah shows a comprehensive style of interpretation with multi-disciplinary approaches. The interpretation of the verses on the concept of al-Muwalah by az-Zuhayli reflects that his interpretation is not only traditional, but also contains dynamic, tolerant, moderate, and humanist principles. The article also concludes that al-Munir's interpretation is included in the category of literary interpretation (al-adabi waal-ijtima'i), not the interpretation of socio-political movements (Adab-ijtima'i-siyasi-haraki).